Enriched LPS Staining within the Germinal Center of a Lymph Node from an HIV-Infected Long-Term Nonprogressor but Not from Progressors - Lei Huang; Jianning Deng; Ren Lang; Guoyang Liao; Wei Jiang (Journal of Immunology Research)
An increased level of microbial translocation has been observed in HIV-infected individuals. The host response to microbial translocation is compromised in HIV-infected progressors but remains unknown in HIV-infected long-term nonprogressors (LTNPs). To evaluate microbial translocation in HIV, we assessed lipopolysaccharide (LPS) immunohistochemistry staining in lymph nodes. We found enriched bacterial LPS immunohistochemistry staining in the germinal center of a lymph node from an HIV-infected LTNP, evenly distributed from three progressors with impaired germinal center structures and rarely detected from two HIV-negative individuals. The impaired germinal center structures were consistent with collagen deposition in lymph nodes using immunohistochemistry staining. These results suggest greater immune responses against bacterial LPS translocation in LTNPs, which may reveal an important mechanism in controlling microbial translocation and disease progression in HIV LTNPs.